The Mueller report : the leaked investigation into President Donald J. Trump and his inner circle of con men, circus clowns, and children he named after himself - Gilbert, Jason O. (Simon & Schuster Paperbacks, 2018)
The most anticipated literary event of the time: the publication of The Mueller Report, the full, uproarious, and Totally Fake findings of Robert Mueller's investigation into the election of President Donald J. Trump, leaked to the Very Biased and Highly Unemployed comedy writer Jason O. Gilbert by an anonymous, Deep Throat-esque source known only as 'Melania T.'